Педагогикалық оқу орындарында кәсіби құзыреттілікті қалыптастырудың жолдары - Ильясова, Р.К.; Нұрашева, Г.С. (My University, 2013)
The papersummarizes thecharacteristics of itsthemes,the worksof Russianand foreign- scientistsstudiedthe theoretical and practicalaspects of the formationof professional competence.Lists the newgoals of educationfornew viewsof modern scienceof pedagogy.The definitions ofnotions ofcompetence, professionalcompetence,information competence, communicative competence, competence to addressself-managementandin the writings ofrenowned scholars.